Deterministic and probabilistic multi-modal analysis of slope stability. (May 2015) - Reale, Cormac; Xue, Jianfeng; Pan, Zhangming; Gavin, Kenneth
Abstract: Traditional slope stability analysis involves predicting the location of the critical slip surface for a given slope and computing a safety factor at that location. However, for some slopes with complicated stratigraphy several distinct critical slip surfaces can exist. Furthermore, the global minimum safety factor in some cases can be less important than potential failure zones when rehabilitating or reinforcing a slope. Existing search techniques used in slope stability analysis cannot find all areas of concern, but instead converge exclusively on the critical slip surface. This paper therefore proposes the use of a holistic multi modal optimisation technique which is able to locate and converge to multiple failure modes simultaneously. The search technique has been demonstrated on a number of benchmark examples using both deterministic and probabilistic analysis to find all possible failure mechanisms, and their respective factors of safety and reliability indices. The results from both the deterministic and probabilistic models show that the search technique is effective in locating the known critical slip surface while also establishing the locations of any other distinct critical slip surfaces within the slope. The approach is of particular relevance for investigating the stability of large slopes with complicated stratigraphy, as these slopes are likely to contain multiple failure mechanisms.